I22 Intranasal administration of mesenchymal stem cells ameliorates the abnormal dopamine transmission system and inflammatory reaction in the R6/2 mouse model of huntington disease. (September 2018) - Yu-Taeger, Libo; Stricker-Shaver, Janice; Arnold, Katrin; Bambynek-Dziuk, Patrycja; Novati, Arianna; Singer, Elisabeth; Claire, Fabian; Magg, Janine; Riess, Olaf; Stolzing, Alexandra; Danielyan, Lusine; Nguyen, Hoa Huu Phuc
Abstract : Background: Huntington disease (HD) is a fatal neurodegenerative disease that currently has no effective treatment. Although intrastriatal administration of mesenchymal stem cells (MSCs) has shown beneficial effects in HD rodent models, its invasive nature and potential host immune reactivity have undermined its clinical use. Hence, we aim to evaluate the non-invasive intranasal administration (INA) as an effective alternative route for delivering MSCs in HD. Methods: MSCs at passage 3 were intranasally administered to 4-week-old R6/2 mice and their survival rate, motor function and locomotor activities were evaluated until 11 weeks of age. Expression levels of inflammatory regulators and proteins involved in dopamine neurotransmission were analyzed using real-time PCR and Western blot in the 11-week-old mice. Results: When compared to PBS-treated R6/2 littermates, MSCs-treated R6/2 mice showed an increased survival rate, decreased body weight loss at a later disease stage and attenuated sleep disturbance. MSCs treatment also increased protein expression levels of DARPP-32 and tyrosine hydroxylase (TH) and restored increased gene expression of inflammatory modulators. Conclusions: Our results demonstrate significantly ameliorated phenotypes of R6/2 mice after MSCs administration via INA. This indicates that INA is an effective delivering route of MSCs to the brain for HD therapy.